Experimental Study on The Performance Characteristics of 4 Stroke CI Engine using Biodiesel Blend from Coconut Oil - suardi suardi; Feston Sandi Paribang; Wira Setiawan; Amalia Ika Wulandari; Muhammad Uswah Pawara; Andi Mursid Nugraha Arifuddin; Alamsyah Alamsyah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
To address the challenges faced by the government in the realm of petroleum imports, a promising strategy was adopted in the utilization of biodegradable and renewable sources of biodiesel, such as coconut oil. This research employed two distinct methodologies: Transesterification for biodiesel synthesis and a comprehensive assessment of fuel properties. Subsequently, an experimental phase assessed biodiesel within an engine environment to analysis performance metrics. Results showed that B30 (30% coconut oil, 70% diesel oil) has density of 0.850 g/cm³, B50 (50% coconut oil) at 0.861 g/cm³, and B100 (Pure coconut oil) at 0.893 g/cm³. The values differed from regional standards. As per ASTM D6751, B30 has a viscosity of 2.31 cSt, B50 3.22 cSt, and B100 is 7.02 cSt. Engine performance revealed B50 with the highest torque at 11.787 Nm, while B0 (pure hydrocarbon diesel) has a thermal efficiency of 38%. B0’s lowest SFC (Specific Fuel Consumption) is 261.12 g/kWh at 2000 watts load and 1000 rpm. Biodiesel coconut oil provided comparable power and torque (0.3% difference from B0) but consumed more fuel (21.6 % higher usage than B0). Keywords:  Biodiesel, Coconut oil, Engine performance, Fuel properties, Transesterification.